Do "green" state measures make import patterns "climate-friendly"? The case of the Asia-Pacific region - Martin Wermelinger (FIW - Research Centre International Economics, 2012)
This paper estimates to what extent "green" crisis-era measures have an impact on the "climate-friendliness" of imports in the Asia-Pacific region. Testable predictions and the empirical strategy are derived from the seminal paper of Eaton and Kortum (2002). The empirical results show that at the intensive margin implemented "green" measures are associated with an increase of sourcing from more rather than less energy intensive countries. One reason for this surprising result may be that governments have presented the state interventions as being "green" although the main purpose was not the environment. At the extensive margin, results are slightly more promising. The implementation of "green" measures seems to decrease the likelihood that imports are sourced from a relatively more energy intensive origin. However, the results are not very strong as to statistical and economic significance. In sum, only limited evidence for environmental benefits of "green" crisis-era interventions through the import channel exist. The implementation of such measures may in fact be associated with an environmental degradation of imports. Moreover, supplier countries being "close" competitors to the interventionist country (in terms of technology levels) relatively loose import share if discriminatory "green" measures are implemented. Stated differently, the alleged "green" measures protect domestic against foreign suppliers with similar technology levels.
Keywords: F13; F18; 330; international trade; trade policy; green growth